Assessment of the magnitude and recent trends in satellite-derived ground-level nitrogen dioxide over North America. (October 2015) - Kharol, S.K.; Martin, R.V.; Philip, S.; Boys, B.; Lamsal, L.N.; Jerrett, M.; Brauer, M.; Crouse, D.L.; McLinden, C.; Burnett, R.T.
Abstract: We estimate ground-level nitrogen dioxide (NO2 ) concentrations from the OMI (Ozone Monitoring Instrument) over North America for the period 2005–2012. A chemical transport model (GEOS-Chem) is used to account for effects of the NO2 profile on the column retrieval, and to relate OMI NO2 columns to ground-level concentrations. The magnitude of the period-mean OMI-derived NO2 concentrations is evaluated versus in situ measurements from air quality networks yielding a significant spatial correlation (r = 0.81) but OMI-derived values are lower with a slope of 0.4. Comparison of the in situ concentrations versus spatially resolved concentrations estimated from land use regression models reveals that this difference partially arises from representativeness difference due to preferential placement of in situ monitors at locations with enhanced NO2, coupled with the OMI horizontal resolution. In situ observations provide information about local concentrations while OMI offers area-averaged information. The remaining difference is less readily explained and appears to include a combination of the effects of local unresolved geophysical processes affecting both the NO2 retrieval and the vertical profile used to relate the column to ground level. We also evaluate trends over North America from OMI and in situ measurements for the period of 2005–2012. OMI derived ground-level NO2 well reproduces the spatial pattern of the in situ trends (r = 0.77) and the slope of 0.4 versus the trend from in situ monitors is consistent with the slope versus mean concentrations. Absolute regional trends inferred from in situ measurements alone may overestimate area average changes. Nonetheless coincidently sampled ground-level NO2 concentrations from OMI and in situ measurements for 2005–2012 exhibit similar relative decreases over Eastern (−6.5 ± 2.0%/yr, −7.1 ± 1.3%/yr), Western (−4.5 ± 1.1%/yr, −6.5 ± 0.7%/yr) and Central (−3.3 ± 2.3%/yr, −4.1 ± 0.8%/yr) North America. Highlights: Trends in OMI-derived surface NO2 are significantly correlated with in situ. Absolute concentrations and trend from in situ are twice those from satellite. This representativeness difference arises from spatial averaging vs. point values. In situ monitors tend to be in locations with elevated NO2 . Satellites offer additional information in regions without monitors.